A COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE OF NON-BANK FINANCIAL INSTITUTIONS IN BANGLADESH - Akber, S. M.; Barua, Dhiman (American Finance & Banking Review, 2021)
NBFIs play an important role in economic development through ensuring proper mobilization of funds in Bangladesh. This study represents a comparison of nine NBFIs operating their business in Bangladesh within the period from 2016 to 2019 through using financial ratios and other measures. To analyze the financial performance this study has used ratio analysis, such as ROA, ROE, ROCE, Institutional size/ Total assets and total equity etc. The outcome of this study says that for generating return the NBFIs performance based on efficiency ratio is different from the performance based on liquidity ratio, capital ratio and other financial measures. This study suggests to NBFIs to be more conscious about loan selection and establish a brand image through providing more efficient services. It also suggests the NBFIs to finds more income generating areas to be more competitive. In the coming years NBFIs will have more prospects that will ensure the economic development of our country.  JEL Classification Codes: F36, L25, G23.